Analysis of Production Factors Influences of Pineapple Farming in Kualu Nenas Village Tambang Sub-District, Kampar Regency - Rajagukguk, Samprida; Yusri, Jum’atri; Muwardi, Didi (Politeknik Pertanian Negeri Payakumbuh, 2021)
Kualu Nenas Village is a center of pineapple production in Tambang District, Kampar Regency. Pineapple production and productivity for the last seven years in Tambang District were fluctuating and decreasing every year. Pineapple farming is the main source of income in the village and has not been managed properly by using its production factors. This study aims to describe the performance of pineapple cultivation by farmers and to analyze the effect of the number of production factors on pineapple productivity. This research was conducted in Kuala Nenas Village. The method of analysis using descriptive statistics and multiple linear regression analysis. The data used is time-series data in the form of cross-section data from pineapple production data in Kualu Nenas Village for a period of four months, starting from November 2019 to February 2020 from direct interviews with 35 farmers using the purposive sampling method. The results of the study conclude that the management of pineapple cultivation at of loosening the soil, weeding, controlling pests and diseases, fertilizing, giving ethrel, thinning tillers, and harvesting activities. The results of the analysis show that the variation in the total productivity of each farmer is 86,20percents due to differences in the use of production factors per hectare. Of the seven production factors that are thought to affect the productivity of the pineapple, only three production factors have a statistically significant effect, namely the use of pineapple staple population with a production elasticity of 0,398percents, the labor usage with a production elasticity of 0,325percents and the use of amount ethrel with a production elasticity of 0,103percents. While, four factors production which did not significantly influence the productivity of pineapples namely the amount of KCL fertilizer, urea fertilizer, ash fertilizer, and ZA fertilizer because the elasticity of production is less than 1 percent. The Return to Scale (RTS) condition of the business is in the Decreasing Return to Scale (DRS) condition with a value of 0,885.